2013
DOI: 10.2337/dc13-0234
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Naltrexone Sustained- Release/Bupropion Sustained-Release Combination Therapy on Body Weight and Glycemic Parameters in Overweight and Obese Patients With Type 2 Diabetes

Abstract: OBJECTIVETo assess the efficacy and safety of 32 mg naltrexone sustained-release (SR)/360 mg bupropion SR (NB) in overweight/obese individuals with type 2 diabetes with or without background oral antidiabetes drugs.RESEARCH DESIGN AND METHODSThis was a 56-week, double-blind, placebo-controlled study in which 505 patients received standardized lifestyle intervention and were randomized 2:1 to NB or placebo. Coprimary end points were percent weight change and achievement of ≥5% weight loss. Secondary end points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
300
3
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 387 publications
(331 citation statements)
references
References 34 publications
10
300
3
18
Order By: Relevance
“…37 The COR-Diabetes trial was restricted to patients with T2DM and utilized a low-intensity lifestyle intervention similar to COR-I and COR-II. 38 Bupropion plus naltrexone caused 4% to 5% of body weight more weight loss than placebo in patients without DM and approximately 3% more in patients with DM. The proportion of patients achieving ≥5% weight loss was greater in the treatment group of all 4 trials.…”
Section: Potential Benefits Of Modern Pharmacotherapy For Obesity Phementioning
confidence: 94%
See 1 more Smart Citation
“…37 The COR-Diabetes trial was restricted to patients with T2DM and utilized a low-intensity lifestyle intervention similar to COR-I and COR-II. 38 Bupropion plus naltrexone caused 4% to 5% of body weight more weight loss than placebo in patients without DM and approximately 3% more in patients with DM. The proportion of patients achieving ≥5% weight loss was greater in the treatment group of all 4 trials.…”
Section: Potential Benefits Of Modern Pharmacotherapy For Obesity Phementioning
confidence: 94%
“…35 -38 In patients with DM, bupropion plus naltrexone reduced HbA 1c more than placebo (−0.6% vs −0.2%). 38 …”
Section: Potential Benefits Of Modern Pharmacotherapy For Obesity Phementioning
confidence: 99%
“…[11][12][13][14] In NB-treated clinical trial completers, nausea, constipation and headache were the most frequently reported AEs with greater incidence than placebo.…”
Section: Safetymentioning
confidence: 99%
“…The COR clinical trials were conducted between March 2007 and June 2009 and the data have been published previously. [11][12][13][14] Participants were 18-65 years old with a body mass index (BMI) 30-45 kg m − 2 , or BMI 27-45 kg m − 2 and dyslipidemia and/or controlled hypertension, except for the COR-DM clinical trial, which included participants with type 2 diabetes mellitus (DM, HbA1c from 7-10% and fasting blood glucose o270 mg dl − 1 ), aged 18-70 years, and with a BMI 27-45 kg m − 2 .…”
Section: The Phase 3 (Cor) Programmentioning
confidence: 99%
See 1 more Smart Citation